The Societal Role of Media in Pakistan: An Analysis in an Islamic Perspective - Ambreen Abbasi (MEI, 2023)
Pakistan as an Islamic state has faced a fundamental social and cultural change in the last fifteen years. Media has touched everything and has made available everything with shortest possible routes. It has since affected human thinking and conduct triggering both positive and negative outcomes in the social, cultural and religious milieu of Pakistan. Eastern (mostly Indian) and western cultures influences are gradually making in-roads into Islamic polity and developing into a new fashions and practices, alien to basic Islamic ideology. It is important that media policies and laws need to be reviewed by the concerned in context of the social, cultural and religious impact it is causing to our society and to bring it into conformity with the precepts of Islam as demanded in the constitution of Pakistan. The aim of the study is to analyze recent Media trends in Pakistan particularly in context of social and religious influence that needs an in depth and without delay, analysis of issues, to avoid any sociological and ideological adverse effects in Pakistan for future generations. Mainly qualitative research methodology along with socio legal methodology is utilized for the research, and wherever required analytical approach has also been followed. The study has been divided into three sections; the first part begins with the introduction of issue at hand and discusses the media in general and its role in a society including the various types of media and influence on behaviors/thinking patterns of society. The second part highlights the influence of media on the religious affiliations of the people and its effect on social behavior in this regard. The third part deals with media in Pakistan and legal frame work for it its regulation. The outcome of the discussion is included in the conclusion at the end.